Perspectives of Patients With Relapsed and Refractory Acute Myeloid Leukemia and High-Risk Myelodysplastic Syndrome on Patient–Clinician Communication About Prognosis and the Future - Vinay Rao; Sarah Linsky; M. Tish Knobf (Palliative Medicine Reports)
Background: Patients with acute myeloid leukemia (AML) and high-risk myelodysplastic syndrome (MDS) experience unpredictable disease trajectories and high prognostic uncertainty, which serve as barriers to patient–clinician communication about prognosis and their values and preferences for the future in the event of worsening health. Little is known about patients' day-to-day lived experiences and how this shapes their willingness to engage in such conversations. Objectives: To explore participant perspectives on living with their illness and patient–clinician communication about prognosis and the future. Design: This is a qualitative study using semi-structured interviews. Setting/Subjects: Patients with relapsed and refractory (R/R) AML and high-risk MDS from a northeastern U.S. cancer center. Data Collection: Interviews were transcribed verbatim and thematic analysis was used to generate findings. Results: Of the 14 participants, the mean age was 66 years, 79% were men, 93% were White, married, and had AML. The overarching theme that describes the experience was “Taking One Day at a Time” in a Fog of Uncertainty. Uncertainty was a universal perception related to the challenges for clinicians to predict prognosis. To cope with uncertainty, most participants tried to focus on the present and maintain normality in everyday life. Participants valued encouragement and positivity in patient–clinician communication, however, the majority were not ready to discuss prognosis and the future in the event of worsening health. Of note, 7 of 14 participants died within three months after the interview. Conclusions: These data describe a unique perspective of patients with R/R AML and high-risk MDS that clinicians could use to enhance communication strategies.